A reversible fluorescent chemosensor for selective and sequential detection of copper ion and sulfide. (February 2016) - Li, Caimei; Liu, Zhixue; Miao, Yu; Zhou, Xin; Wu, Xue
Abstract: We reported here a reversible fluorescent chemosensor CPO for sequential recognition of Cu 2+ and S 2− in aqueous and biological media. This sensor CPO showed highly selective binding towards Cu 2+ along with a fluorescence quenching due to the formation of the corresponding complex (CPO)2 –Cu 2+ . And this phenomenon could be reversed in the presence of S 2−, resulting in the recovery of its initial intense fluorescence. Moreover, sensor CPO showed a highly sensitive and selective response towards Cu 2+ and S 2− over other metal ions and anions. Particularly, the fluorescence "ON-OFF-ON" responding circle could be repeated over 5 times by the sequential addition of Cu 2+ and S 2− . More important, the actual usage of sensor CPO in the cell imaging study was further demonstrated by confocal fluorescence imaging with living cells. The cellular toxicity and quantification studies in single intact cell were also exploited by the flow cytometry analysis. Graphical abstract: We present here a reversible fluorescent chemosensor CPO for sequential recognition of Cu 2+ and S 2− in aqueous and biological media. Its potential utility in living HeLa cells by using fluorescence confocal microscopy was investigated. The cellular toxicity studies indicated that our sensor CPO showed low toxicity. Highlights: A reversible chemosensor CPO was constructed for sequential recognition of Cu 2+ and S 2− . The fluorescence confocal imaging was investigated with living HeLa cells. The low cytotoxicity of sensor CPO was demonstrated by flow cytometry analysis.